Pengaruh Literasi Media Massa Online Terhadap Civic Engagement Politik Aktivis Mahasiswa - Gofur, Abdul; Sunarso, Sunarso (Universitas Negeri Malang, 2019)
The purpose of writing this article is to describe the effect of online mass media literacy on civic engagement of student activists in the political field. This type of survey research with a quantitative approach. The population was 651 students and a sample of 90 students. Data analysis uses descriptive statistical analysis and simple regression. Online mass media literacy has a significant and positive influence on civic engagement in politics. The results of data analysis show the value of t-count is greater than the t-table (10,332>1,986). The significance value is smaller than alpha (0,000 <0.05). The contribution of Mass Media Online Literacy to Civic Engagement in politics in student activists was 54.8%, while the rest was influenced by other factors.